2016
DOI: 10.1016/j.atmosenv.2016.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deep injection on field-scale emissions of 1,3-dichloropropene and chloropicrin from bare soil

Abstract: Atmospheric emissions of 1,3-dichloropropene (1,3-D) and chloropicrin can be reduced by deep injection into soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Modeled cumulative volatilization after 14 days was 24.5% of 66.5 kg/ha application of cis-1,3-D. Previous field studies near Buttonwillow, CA ( Yates et al , 2008 , 2015 , 2016 ) found 16-35% cumulative flux of bare soil 1,3-D application. van Wesenbeeck et al (2007) measured 1,3-D flux of 26.5% at a field site near Douglas, GA. Brown et al (2019) simulated 10 to 58% volatilization losses of 1,3-D for 17 different application methods using HYDRUS model.…”
Section: Resultsmentioning
confidence: 85%
“…Modeled cumulative volatilization after 14 days was 24.5% of 66.5 kg/ha application of cis-1,3-D. Previous field studies near Buttonwillow, CA ( Yates et al , 2008 , 2015 , 2016 ) found 16-35% cumulative flux of bare soil 1,3-D application. van Wesenbeeck et al (2007) measured 1,3-D flux of 26.5% at a field site near Douglas, GA. Brown et al (2019) simulated 10 to 58% volatilization losses of 1,3-D for 17 different application methods using HYDRUS model.…”
Section: Resultsmentioning
confidence: 85%
“…AERMOD replaced ISCST3 by USEPA, although ISCST3 is still in use by some researchers and regulatory authorities. ISCST3 has been widely used to simulate probability distribution functions (PDFs) of fumigant concentrations in air within townships in California to estimate acute and chronic bystander exposure [15,16].…”
Section: Air Dispersion Modelmentioning
confidence: 99%